Adenoid cystic carcinoma and chronic lymphocytic leukaemia: synchronous presentations in the lung. Issue 2 (24th February 2021) - Webb, Philip S; Zhang, Yu Zhi; Burrell, Kirsten; Sinclair, Georges
Abstract : A 59-year-old male active smoker presented with a 6-month history of cough and breathlessness and was found to have a right upper lobe mass. Histology revealed this to be an adenoid cystic carcinoma (ACC) of the lung, while local lymph node dissection revealed a synchronous diagnosis of chronic lymphocytic leukaemia (CLL). The connection between CLL and solid organ malignancy is well documented, but the reporting of ACC in this context is novel. Mechanisms linking the two processes are revealed with the possibility of causality, and heightened vigilance for the development of primary lung tumours in CLL, and their management, is recommended.